Stakeholder engagement and organisational interest in ecotourism development at brumas forest plantation - Tampokong, Mohd Daud; Farizan, Noor Hamzani; Yazid, Abdullah Zawawi; Yaakob, Sam Shor Nahar (Goodwood Publishing, 2025)
Purpose: This study examined stakeholder engagement and organisational interest in ecotourism development at Brumas Forest Plantation, Sabah. It explored local communities’ perceptions, participation barriers, and the role of Sabah Softwoods Berhad (SSB) in promoting sustainable tourism initiatives. Research Methodology: A mixed-methods approach was employed, integrating survey, interview, and focus group discussion (FGD). Data were collected from 250 local residents and nine SSB personnel. Quantitative data were analysed using SPSS, while qualitative data underwent thematic analysis using ATLAS.ti. Results: 88.4% of the respondents recognised the ecotourism potential but only 19.2% actively participated. Main barriers included poor infrastructure (74.0%), limited promotion (69.6%), and insufficient government support (66.8%). Despite this, communities expressed interest if structured programmes, training, and economic incentives were provided. SSB supported ecotourism but emphasised the need for clear policies and collaborative frameworks. Conclusion: Effective development requires coordinated stakeholder engagement, strategic planning, and community empowerment. Corporate efforts alone are insufficient without addressing local barriers and governance support. Limitations: The study was limited to Brumas, reducing generalisability to other contexts. Contributions: This research integrates community and corporate views to offer practical strategies for bridging the gap between ecotourism potential and participation. It contributes to literature on sustainable tourism, rural development, and CSR.